A spiropyran–coumarin platform: an environment sensitive photoresponsive drug delivery system for efficient cancer therapy. Issue 21 (11th May 2017) - Barman, Shrabani; Das, Joyjyoti; Biswas, Sandipan; Maiti, T. K.; Pradeep Singh, N. D.
Abstract : In spite of inventing several anticancer agents the clinical payoff still remains unsatisfactory because of their severe host toxicity due to their nonspecific biodistribution in the body. Abstract : In spite of inventing several anticancer agents the clinical payoff still remains unsatisfactory because of their severe host toxicity due to their nonspecific biodistribution in the body. To achieve high efficiency in anti-cancer drug delivery, thus, we designed and developed a single component photoresponsive drug delivery system, a fusion of two platforms spiropyran and coumarin, which synchronizes two controlling factors: first, the lower pH of cancer tissue, which acts as an internal control and leads to the ring opening of spiropyran resulting in a distinct colour change and fluorescence activation of coumarin; and second, the release of the anti-tumor drug by the externally controlled light. Highly fluorescent nature and promising biocompatibility make theSP–Cou–Cbl system suitable for cell imaging and in vitro studies.